The Impact of Government Trust and Government Advertising Believability on Climate Change Government Advertising - Jong Woo Jun; Jungryum Kim (SAGE Open)
This study investigated how consumers perceive government advertising about climate change. The effectiveness of government advertising itself is important, but trust in the government can also affect government advertising as it reflects the government’s philosophy. As a result of a survey of the general public, it was found that involvement in climate change had a positive effect on attitudes toward government advertising and behavioral intention to participate in climate change campaigns. Trust in the government influenced attitudes toward government advertisements and behavioral intention to participate. Advertising value was also found to have a positive effect on both dependent variables. Advertising believability only affected advertising attitude. In the final model, the influence of trust in government disappeared in both advertising attitude and participation intention. These results show the role of personal and advertising variables on the effectiveness of government advertising on climate change and provide implications both academically and practically.